Northern men with Southern loyalties : the Democratic party and the sectional crisis - Landis, Michael Todd (Cornell University Press, 2014)
"In Northern Men with Southern Loyalties, Michael Todd Landis forcefully contends that a full understanding of the Civil War and its causes is impossible without a careful examination of Northern Democrats and their proslavery sentiments and activities. He focuses on a variety of key Democratic politicians, such as Stephen Douglas, William Marcy, and Jesse Bright, to unravel the puzzle of Northern Democratic political allegiance to the South. As congressmen, state party bosses, convention wirepullers, cabinet officials, and presidents, these men produced the legislation and policies that led to the fragmentation of the party and catastrophic disunion."--Jacket